Investigating pulmonary and non-infectious complications in common variable immunodeficiency disorders: a UK national multi-centre study - Bintalib, Heba M.; Grigoriadou, Sofia; Patel, Smita Y.; Mutlu, Leman; Sooriyakumar, Kavitha; Vaitla, Prashantha; McDermott, Elizabeth; Drewe, Elizabeth; Steele, Cathal; Ahuja, Manisha; Garcez, Tomaz; Gompels, Mark; et al. (Frontiers in immunology, 2024)
Common Variable Immunodeficiency Disorders (CVID) encompass a spectrum of immunodeficiency characterised by recurrent infections and diverse non-infectious complications (NICs). This study aimed to describe the clinical features and variation in NICs in CVID with and without interstitial lung disease (ILD) from a large UK national registry population. Retrospective, cross-sectional data from a UK multicentre database (previously known as UKPIN), categorising patients into those with CVID-ILD and those with NICs related to CVID but without pulmonary involvement (CVID-EP; EP= extra-pulmonary involvement only). 129 patients were included. Chronic lung diseases, especially CVID-ILD, are prominent complications in complex CVID, occurring in 62% of the cohort. Bronchiectasis was common (64% of the cohort) and associated with greater pulmonary function impairment in patients with CVID-ILD compared to those without bronchiectasis. Lymphadenopathy and the absence of gastrointestinal diseases were significant predictors of ILD in complex CVID. Although the presence of liver disease did not differ significantly between the groups, nearly half of the CVID-ILD patients were found to have liver disease. Patients with CVID-ILD were more likely to receive immunosuppressive treatments such as rituximab and mycophenolate mofetil than the CVID-EP group, indicating greater need for treatment and risk of complications. This study highlights the significant burden of CVID-ILD within the CVID population with NICs only. The lungs emerged as the most frequently affected organ, with ILD and bronchiectasis both highly prevalent. These findings emphasise the necessity of a comprehensive and multidisciplinary approach in managing CVID patients, considering their susceptibility to various comorbidities and complications.